Cities and the larger context: What explains changing levels of crime?. (March 2017) - Hipp, John R.; Kane, Kevin
Abstract: This study explores whether the broader context in which a city is located impacts the change in crime levels over the subsequent decade. This study uses a wide range of cities (those with a population of at least 10, 000), over a long period of time (from 1970 to 2010). We test and find that although cities with larger population and those surrounded by a county with a larger population typically experience larger increases in crime over the subsequent decade, cities experiencing an increase in population during the current decade experience crime decreases. The study finds that cities with higher average income experience greater subsequent crime decreases, and those surrounded by counties with larger unemployment increases experience crime increases. Higher levels of income inequality and racial/ethnic heterogeneity are associated with increasing crime rates, and increasing inequality and racial/ethnic heterogeneity in the surrounding county are associated with further increases. Furthermore, this relationship has strengthened since 1970, suggesting that both scales of inequality are even more important from a public safety perspective. Finally, we tested the time invariance of these relationships, and showed that the magnitude of the relationship between city-level inequality and increasing crime has increased over the study period. Highlights: Tests the impact of the broader context on changes in city crime levels. Cities experiencing increasing population in the decade experience crime decrease. Greater population in surrounding area results in larger crime increases in cities. Increasing inequality and racial heterogeneity in surrounding areas results in crime increases. Relationships for inequality and heterogeneity have strengthened from 1970 to 2010.